ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP LOYALITAS DESTINASI DIMEDIASI CITRA DESTINASI DAN KEPUASAN WISATAWAN (Studi Kasus Pada Wisata Paralayang Kota Batu) - Moh. Rizal; N Rachma; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTSince the development of internet technology which is a network system that has become one of the facilities for companies to market a product or service to consumers. With social media that is heard today is no stranger, the growth of the internet is increasingly widespread and more and more are using it so that through internet sites such as Facebook, Istagram and other social media easily an information is quickly conveyed via the internet or can be called electronic word of mouth (e-wom) includes paralayang tourism information which is now one of the trends on social media.The spread of information carried out by tourism objects on social media with a delivery process that is elegantly designed so that someone's decision to visit tourism is created. After that, providing a pleasant service with a variety of products that are in line with the market so that customers will be satisfied with what is seen on social media and indirectly the customer will communicate with others by discussing electronic word of mouth, destination image, tourist satisfaction, and destination loyalty. The results of the study provide electronic word of mouth information, destination image, and tourist satisfaction have a significant positive effect on destination loyalty, and the destination image mediates the effect of electronic word of mouth on destination loyalty, and tourist satisfaction mediates the effect of electronic word of mouth on destination loyalty.Keywords: Electronic word of mouth, destination image, tourist satisfaction, Destination loyalty